Insights Into Wire Rope Safety Barrier Crashes Based on Police-Reported Statistics and Narratives - Nimmi Candappa; Janneke Berecki-Gisolf; David Logan (Journal of Road Safety, 2023)
Wire rope safety barrier (WRSB) is known to be highly effective in reducing the severity of off-road or off-path crashes, however fatal and serious injury outcomes still occur in a small percentage of WRSB-involved crashes. Yet, there is little research on why some WRSB crashes result in severe injury while the majority of crashes involve minor injury outcomes. This paper includes detailed analysis of off-path crashes involving WRSB to better understand associated factors that contribute to severe injury outcomes. Three datasets were analysed: four years of NSW police-reported crash data (2014-2017); ten years of Victorian police-reported crash data and police narratives (2008-2017); five years of police narratives from the US (2001-2005). Results supported earlier research that indicated a relatively low percentage of WRSB crashes involved fatal and serious injury outcomes. Yet, adverse vehicle dynamics were also observed, such as vehicle ricochetting and barrier override, suggesting barrier safety performance could be improved. Some crashes also involved impact angles greater than those used in crash tests, supporting earlier, more detailed research that the full range of real-world crash conditions involving WRSB are not covered in barrier test protocols, and these might be the conditions contributing to severe injury outcomes. The findings provide insight into the potential factors associated with the serious injury outcomes of crashes and can guide further improvements in this effective highway crash countermeasure. Future research should include detailed analysis of real-world crashes to identify factors contributing to adverse crash dynamics, injury outcomes and subsequent implications for barrier design.